Use of Cognitive Work Analysis for exploration of safety management in the operation of motorcycles and scooters. (January 2015) - Regan, Michael A.; Lintern, Gavan; Hutchinson, Robin; Turetschek, Christine
Abstract: The risk of accident, injury and death is disproportionately higher for motorcycle riders than for motorists. In this paper, we investigate strategies of safety management associated with operation of powered two-wheel vehicles (motorcycles and scooters). Accident prevention is most often driven by an epidemiological approach that investigates the risk factors associated with accidents. By focusing on risk factors, these types of studies fail to examine the strengths of the system in any depth. In this paper we employ an ethnographic approach structured by reference to the framework of Cognitive Work Analysis, to identify how riders of powered two-wheel vehicles manage their own safety and the safety of others. We anticipate that this research will open up a rich, relatively untapped, area for exploration of safety interventions.